Integrating virtual reality and problem-based learning in STEM education: A contextual approach to enhance mathematical literacy through cultural heritage - Munzid Mahendra; Nanik Asriyah Ismawati; Adi Nur Cahyono (Universitas Hamzanwadi, 2025)
Mathematical literacy is an essential competency in mathematics education that plays a crucial role in equipping students to meet the demands of the 21st century. However, students' mathematical literacy in Indonesia remains low. This study aimed to investigate how problem-based learning (PBL) with virtual reality (VR) technology in STEM education, contextualised within the complex of Arjuna Temple in Dieng, could be designed to enhance mathematical literacy. The study employed a design research method involving tenth-grade students at a senior high school in Wonosobo, Indonesia. Qualitative techniques were used to analyse students' responses to the implemented learning, while quantitative techniques were applied to analyse students' pretest and posttest results. The study produced a learning design validated by three experts and deemed practical by five practitioners. The results indicated a significant improvement in students' pre- and post-test scores. Students also provided positive feedback regarding the developed learning program. Given these results, Problem-Based Learning with Virtual Reality STEM education technology contextualised to the Arjuna Dieng Temple complex was considered a viable approach to enhancing mathematical literacy.